10–9 Challenging scenarios in primary care – learning opportunities for nurses and allied healthcare professionals. (17th November 2017) - O'Shaughnessy, Nicola; Nightingale, Kari; Lyon-Maris, Johnny
Abstract : Background: The GP Education Unit secured funds to provide professional development and education sessions for qualified nurses, healthcare assistants and primary care allied healthcare professionals to develop or improve their skills in dealing with challenging encounters in the workplace. There is good evidence that simulated scenarios for clinical staff provide effective learning experiences. Our sessions focused on healthcare scenarios that were uncommon but challenging personally and/or ethically; for these reasons clinical staff may find them uncomfortable. Summary of work: Session participants experienced simulated workplace scenarios such as: dealing with professional integrity issues, confidentiality, 'the angry patient' and 'the overly familiar' patient. The sessions took place on site and were co-facilitated by two GP ST4 fellows from the Southampton GPEU and the Simulated Patient Team. Summary of results: Bi-monthly sessions were planned from Spring 2016. Sessions were evaluated from the perspectives of all participants. Feedback from the Southampton City CCG area where we have run sessions to date, has been extremely positive and the facilitators have been asked to provide further sessions in the same practices for staff who were unable to attend. Bookings are also being taken from practices in the neighbouring West Hampshire CCG region. Conclusions: The sessions were found to provide a safe environment for staff to think through challenging situations and test out their reactions, in order to help them feel better equipped to deal with them when they do arise. Results will be shared in the poster and placed in the context of the literature. Take home messages: Excellent healthcare depends on developing a caring, compassionate, highly-skilled and educated workforce, working in a supportive culture. This simulation pilot contributes to these aims by building on individual as well as team skill-sets, and promoting confidence in dealing with challenging scenarios in primary care.